Compact electron linac LU-7-2 for radiography of large-scale objects - Shorikov, I.V.; Zavyalov, N.V.; Inkov, V.I.; Sitnikov, N.P.; Tarantasov, V.P.; Telnov, A.V.; Khokhlov, Yu.A. (Вопросы атомной науки и техники, 2001)
At RFNC-VNIIEF there was started up a compact LU-7-2 linear electron accelerator designed for industrial application in the field of radiography of objects with a large mass thickness as well as for development of radiation technologies. For accelerator microwave power supply there was used a magnetron operating on a wavelength of 10.7 cm with a pulse power of 2.5 MW. Accelerating structure was created on the basis of a circular disc-loaded waveguide with varying geometry of accelerating cells, operating on a traveling wave of 2π/3 mode. Electrons are injected by a diode type 50 kV electron gun. The achieved parameters allow to use the accelerator for radiography of objects with a large mass thickness.